Cost Benefit Analysis of Key Actors in The Cocoa Beans Marketing - Asir, Muhammad; Asir, Annisa Ishmat (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Efficient marketing can increase the profits of all the stakeholders involved. Profit increased at the farmer level will encourage the ability and motivation to manage the farm. This study aims to identify the benefits obtained by farmers, collectors, wholesalers, and purchasing units of exporters in the marketing of cocoa beans. This research was conducted through the survey using by Hayami Method. The results showed that: Profit received by farmers amount Rp314/kg was lower than those received by collectors amount Rp1,022/kg, wholesalers at Rp736/kg, and unit purchases at Rp2,826/kg. This was due to the cost of labor incurred by farmers, and the amount of Rp2,100/kg was higher than by collector's amount of Rp230/kg, the wholesaler's Rp12.5/kg, and the purchase unit Rp8.25/kg. Another factor was the price of production input costly (such as fertilizer dan pesticides), which was not followed by the increase in output price (cocoa beans) determined by marketers. The low productivity and quality of cocoa beans produced by farmers also affected low profit. The government must be able to control the purchase price of marketing actors, improve the knowledge and skills of farmers in the management of cocoa farms by establishing business groups/cooperatives, increase the role of farmer groups, and also to improve the internet infrastructure that supports the digital marketing of cocoa commodities. Keywords: main stakeholders, cocoa beans, profit, marketing, Hayami method